WORK SYSTEM ASPECTS ASSOCIATED WITH PRODUCTIVITY OF RAILWAY STATION FACILITY INSPECTION OFFICERS IN KISARAN - Hasanatun Laili; Tri Niswati Utami; Yulia Khairina Ashar (RADJA PUBLIKA, 2025)
Work productivity is influenced by various factors, one of which is an effective work system. A good work system can provide a sense of security and comfort for workers. This study aims to analyze the relationship between work systems consisting of work motivation, work materials and productivity of facility inspection officers at the Kisaran Railway Station. This study used a quantitative method with a cross-sectional approach. The study population consisted of 43 railway station facility inspectors, with the sampling technique using total sampling. The research instrument was a questionnaire covering three main variables: work motivation (10 questions), work materials (9 questions), and work productivity (9 questions). Data analysis was conducted using multiple linear regression tests. The results of this study concluded that work motivation has no effect on work productivity. Work materials have a positive effect on work productivity. Highly motivated employees will strive to achieve good work productivity and actively contribute to achieving organizational goals.